A Little Goes a Long Way: Treating Sexual Health in Young Adult Cancer Survivors. (1st August 2022) - Chevalier, L; Recklitis, C; Bober, S
ABSTRACT: Introduction: Cancer treatment can significantly disrupt sexual development and result in sexual dysfunction in young adult cancer survivors (YACS). These symptoms and their potential solutions can be understood through a biopsychosocial framework. Specifically, YACS often experience biological sexual health concerns tied to medical late effects of cancer treatment (e.g., erectile dysfunction after surgery). However, timing of treatment can also lead to disruptions in psychosexual development and result in significant psychosocial sexual health concerns (e.g., social isolation during treatment delays first sexual experience). Despite the impairing and distressing nature of these concerns, the majority of YACS do not receive the services they need as part of survivorship care. When treatment does occur, it generally focuses only on physical symptoms rather than the psychosocial concerns common in YACS. However, even brief treatment with YACS that addresses all aspects of the biopsychosocial framework can be transformative. Objective: To demonstrate how sexual health treatment can be tailored to the needs of YACS by presenting two case studies using a biopsychosocial framework. Methods: During this presentation I will: 1) Articulate the comprehensive sexual health needs of YACS. 2) Apply the biopsychosocial framework to YACS' sexual health concerns. 3) Present two clinical cases to illustrate important considerations for addressing sexual health in YACS. Results: Case 1: "Sally" is a 30-year-old survivor treated for brain cancer with surgery as an adolescent. She presented to a cancer sexual health clinic with biological (i.e., vaginal atrophy, pelvic pain), psychological (i.e., anxiety about sexual activity), and social (i.e., embarrassment about lack of sexual experience) concerns. Treatment consisted of an intake and nine sessions. It involved psychoeducation (e.g., female sexual pleasure), a referral to both menopause specialist and pelvic floor physical therapy, and role-plays (e.g., how to communicate with parents about desire for increased independence). Sally made significant progress and described the treatment as meaningful: "I'm not the person I was when I started therapy; I felt like a girl, now I finally feel like a woman." Case 2: "Andrew" is a 24-year-old survivor treated with surgery for testicular cancer as a young adult. He presented to a cancer sexual health clinic with social concerns (i.e., embarrassment about lack of sexual experience). Treatment consisted of an intake and one session; it involved psychoeducation (e.g., normalizing delays in sexual experience in YACS) and role-plays (e.g., how to communicate with potential partners about lack of sexual experience). By the end of treatment, Andrew had his first successful sexual experience with a potential long-term partner. Conclusions: YACS rarely receive the necessary attention for sexual health and when they do, treatment often focuses exclusively on biological dysfunction. However, when a biopsychosocial model is employed and comprehensive care is delivered, significant progress can be made, often in short period of time. As illustrated in these case studies, the addition of psychoeducation normalizing delays in sexual experience in YACS and providing concrete steps to initiate romantic relationships can change lives. In the words of one patient, "I had two brain surgeries but [sexual therapy] saved my life." Disclosure: No